Equine umbilical cord: features during gestation and postpartum evaluation (Research, Society and Development, 2021)
In equines, as other mammalian species, the umbilical cord is the only source of conduction of nutrients, gases, and metabolites from the placenta to the fetus, and its adequate development is super important for fetal health during pregnancy. The aim of the present review is to characterize the umbilical cord during pregnancy in horses, as well as to describe the main changes and casual findings in its evaluation with the placenta and the newborn in the postpartum period. For methodology a qualitative literature review was performed about the characteristics of the umbilical cord in the equine specie using articles selected using Mendeley, MEDLINE, PubMed and SciELO platforms. As a result, we can identify the characteristics of anatomy and development. Moreover, the most common changes in the umbilical cord are the identification of excessive length cords (over 85 cm at term), pathological twisting, or torsion of the cord and changes of uracus. These can be of non-infectious (umbilical hernias and patent uracus) or infectious conditions (omphalopathies). As casual findings, we can find amniotic plaques and ossification of remnants of the umbilical cord and yolk sac. We conclude that the evaluation of the umbilical cord in the immediate postpartum period could help in the recognition of changes not observed during pregnancy, and it is essential to characterize the changes of clinical relevance of the casual findings in evaluation of the umbilical cord in equines.